Vulnerability of Gastric Mucosa to Prednisolone in Rats Chronically Exposed to Cigarette Smoke - Yoshiaki Takeuchi; Maki Takahashi; Jun-ichi Fuchikami (Elsevier, 2008)
We examined gastric mucosal vulnerability in a rat model of chronic obstructive pulmonary disease (COPD). Male Wistar rats were exposed to cigarette smoke for 12 weeks (CSE rats), and on the last 4 days of exposure, prednisolone was given to induce gastric mucosal injury. Histopathology, pulmonary function, arterial blood gases, and levels of lipid peroxides (LPO), prostaglandin E2(PGE2), hypoxia-inducible factor 1 alpha subunit (HIF-1α ), and vascular endothelial growth factor (VEGF) in gastric mucosa were examined. We also tested the effect of rebamipide on prednisolone-induced gastric lesions. In CSE rats, although no gastric lesions were detected, LPO, PGE2, HIF-1α, and VEGF levels were higher than in control rats. Prednisolone induced gastric hemorrhagic lesions more readily in CSE rats than controls, with concomitant decrease in PaO2and increased levels of LPO, HIF-1α, and VEGF. Rebamipide reversed gastric lesions without affecting any parameters examined. CSE rats were found to be a useful animal model of COPD, and COPD appeared to render the gastric mucosa vulnerable to prednisolone. Keywords:: chronic obstructive pulmonary disease (COPD), cigarette smoke, gastric mucosal injury, prednisolone, rebamipide